Understanding Information System Continuance Intention In The Indonesian Public Sector - Prasetyo, Adi; Syaebani, Muhammad Irfan (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
Employing the framework of the Expectation Confirmation Model within the Indonesian public sector context. This research endeavoured to explore the impact of satisfaction, self-efficacy, perceived usefulness, enjoyment, and confirmation on the continuance intention of information systems. The study engaged 436 employees from the Indonesian State Revenue Organization as participants. Utilizing a 7-point Likert scale, online surveys were administered to collect data, subsequently subjected to analysis employing Lisrel 8.8 and Structural Equation Modelling (SEM). The results suggested that self-efficacy and confirmation were strong predictors of perceived usefulness. There existed a strong and positive association between confirmation and satisfaction, perceived usefulness and satisfaction as well as enjoyment and satisfaction. Satisfaction acted as a partial mediation variable between perceived usefulness and continuance intention as well as between enjoyment and continuance intention. Hereafter, the relationship between self-efficacy and continuance intention was influenced by perceived usefulness as the indirect-only mediator. In addition, the relationship between confirmation and continuance intention was influenced by satisfaction as the indirect-only mediator. Ultimately, the continuance intention in information systems was strongly associated with satisfaction, enjoyment,  and perceived usefulness